2009
DOI: 10.1089/ten.tec.2008.0234
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Restriction and Differentiation of Human Embryonic Stem Cells into Hepatic Progenitors and Zone 1 Hepatocytes

Abstract: Human embryonic stem (hES) cells can self-renew, which enables them to have considerable expansion potential, and are pluripotent. If their differentiation can be controlled, they can offer promise for clinical programs in cell therapies. A novel strategy has been developed to derive early hepatocytic lineage stages from hES cells using four sequential inducing steps lasting 16 days. First, embryoid bodies (EBs) were generated by growing hES cells in suspension for 2 days; second, EBs were lineage restricted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Put simply, FGF produced from cardiac mesoderm triggers hepatic buds from the endoderm-originated tube, BMP-4 from septum transversum promotes differentiation and proliferation, cytokine, such as OSM, leads them to the final stage (Duncan, 2003). Many methods to differentiate have been developed and practiced (Cai et al, 2007;Hu et al, 2003;Ishii et al, 2008;Pei et al, 2009;Soto-Gutierrez et al, 2006;Teratani et al, 2005). Curiously, however, they deleted BMP-4 produced from septum transversum, which is an indispensible factor for hepatic development.…”
Section: Induction Of Hepatocyte Differentiation From Human Escs or Imentioning
confidence: 99%
“…Put simply, FGF produced from cardiac mesoderm triggers hepatic buds from the endoderm-originated tube, BMP-4 from septum transversum promotes differentiation and proliferation, cytokine, such as OSM, leads them to the final stage (Duncan, 2003). Many methods to differentiate have been developed and practiced (Cai et al, 2007;Hu et al, 2003;Ishii et al, 2008;Pei et al, 2009;Soto-Gutierrez et al, 2006;Teratani et al, 2005). Curiously, however, they deleted BMP-4 produced from septum transversum, which is an indispensible factor for hepatic development.…”
Section: Induction Of Hepatocyte Differentiation From Human Escs or Imentioning
confidence: 99%
“…All procedures were performed under general (ether) anesthesia using sterile surgical techniques. Hepatocytes were harvested using an in situ two-step ethylenediaminetetraacetic acid/collagenase digestion, as described previously [10] . Isolated hepatocytes with a viability of more than 90% were used for the experiments.…”
Section: Hepatocyte Isolation and Cell Culturementioning
confidence: 99%
“…Pei et al prepared genetically modified FGF-secreting human fetal stromal cells and applied them to human ES cells in the presence of HGF and OSM. They succeeded in obtaining well-defined hepatocyte progenitors and an early stage of hepatocytes [90].…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%
“…Interestingly, they compared two kinds of such 3D pellets, that containing cells alone and cells with small intestinal submucosa (SIS) matrix, and observed hepatic differentiation was much superior in the pellets without SIS matrix. The results seem to suggest that contact with the liver-specific ECM or cells [84,[87][88][89][90] is favorable for hepatic induction of stem cells. Kazemnejad et al also reported hepatic differentiation of human MSCs in 3D culture using poly--caprolactone-based nanofiber scaffolds [98].…”
Section: Adult Stem Cellsmentioning
confidence: 99%